Analysis of Student Satisfaction with Student Affairs Unit Services: A Case Study of the Industrial Engineering Study Program at XYZ University - Utami, Endah; Regita, Dika Brahmanda Ayu (The Indonesian Institute of Science and Technology Research, 2023)
Student satisfaction is a crucial criterion for assessing the quality of higher education. This study aimed to measure student satisfaction with the scholarship service process in a higher education institution. The research employed multiple linear regression analysis using the Servqual model proposed by Parasuraman, which includes the variables of tangibles, responsiveness, reliability, assurance, and empathy. The population of this study consisted of 132 active students from the Industrial Engineering Study Program (IE), enrolled between 2016 and 2019. The partial test results revealed that reliability (Sig. 0.039 < 0.05) and assurance (Sig. 0.000 < 0.05) significantly influenced student satisfaction. The simultaneous test results demonstrated that tangibles, responsiveness, reliability, assurance, and empathy significantly impacted student satisfaction. The correlation coefficient, represented by R2 (0.754), indicated that the variables under investigation could explain 75.4% of the variation in student satisfaction. In comparison, the remaining 24.6% may be influenced by external factors beyond the scope of this study.